Effects of different preceding crops on soil nutrients and foxtail millet productivity and quality - Shi, Chongyan; Qiu, Tian; Zhang, Yangyang; Ma, Yuchao; Li, Xiaorui; Dong, Shuqi; Yuan, Xiangyang; Song, Xi’e (Frontiers in Plant Science, 2024)
Crop rotation can affect crop productivity and soil characteristics; however, the impact of preceding crops on the yield and quality of foxtail millet and the relationship between these two factors have not been well characterised. To further investigate the effects of preceding crops on foxtail millet, this study cultivated maize, mung beans, soybeans, potatoes, and proso millet as the preceding crops and rotated them with Zhangzagu10 foxtail millet. A randomised complete block design was employed for the study, and soil and millet samples were collected after harvest. The performance of Zhangzagu10 foxtail millet grown with five different preceding crops was explored by measuring yield and quality indicators and comprehensively analysing various quality traits and their interrelationships. The physicochemical and nutritional characteristics of millet grains were significantly influenced by the preceding crop. The yield of Zhangzagu10 cultivated after mung bean was significantly higher (8277.47 kg/hm2) than that of millet cultivated after the other crops. Additionally, the colour characteristics (a*, b*, and △E values) were superior, with the rice exhibiting the strongest yellow colour. Foxtail millet preceded by soybean showed a significantly higher thousand-grain weight, indicating well-filled grains. Furthermore, this treatment had rich contents of carotenoids and polyphenols at 34.79 mg/kg and 76.27 mg/100 g, respectively, and significantly higher levels of minerals such as V, Cr, Fe, Co, Ni, Se, and Sn compared to the other treatments. Foxtail millet following mung bean and soybean demonstrated excellent grain quality, featuring high breakage values and gelatinisation, along with low cooking values and gelatinisation temperatures and moderately low setback values. Zhangzagu10 cultivated after potato exhibited a polyphenol content of 67.13 mg/100 g, showcasing strong antioxidant effects. In contrast, proso millet preceded by foxtail millet had relatively lower content levels across various substances, resulting in an overall subpar performance. In summary, selecting appropriate preceding crops can significantly enhance both the yield and quality of Zhangzagu millet. Moreover, soybeans, potatoes, and mung beans can be effectively incorporated into a sustainable crop rotation plan for millet. In the future, we aim to further explore the interaction mechanisms between preceding crops and millet to optimise rotation strategies and improve foxtail millet quality.